Who Lives, Who Dies, Who Tells the Story: Aesthetics of Existence in Never Let Me Go - Chen, Haoyue (Transactions on Social Science, Education and Humanities Research, 2024)
Kazuo Ishiguro’s Never Let Me Go published in 2005 is characterized by the cloned protagonist and narrator. Focusing on her relationship with Tommy and Ruth, the narrator Kathy recalls their childhood experiences as students in Hailsham and their adulthood as carers and donors. This paper argues that the covert progression of the novel reveals Kathy’s growth in her comprehension of mortality. Through the aesthetics of narration, Ishiguro presents the aesthetic of existence using the art of language and creation to face limitations and mortality, throwing light on the redemptive power of art in shaping humanities.